PELATIHAN MANAJEMEN BISNIS UNTUK MENINGKATKAN KINERJA DAN KUALITAS KARYAWAN DENGAN MENGGUNAKAN METODE KPI DI BALI BEACH GLAMPING TABANAN - Ni Made Ratih Anbarini (CV. Multi Kreasi Media, 2023)
In a company, human resources play an important role in improving the company's progress. In this case, companies need to find good methods to improve employee performance. One method that can be used is the KPI (Key Performance Management) method because this really supports how important it is to assess employee performance to achieve company goals. The aim of this training activity is to support companies that own glamping in improving the quality of their employees' performance. Implementation of this training activity for Bali Beach Glamping which is located in the Tabanan area of ​​Bali, method of providing material, tutorials, discussions and simulations. The training is carried out directly or face to face. Number of participants 16 people. Based on the results of the analysis and discussion, 85% of the participants were also ready to use this method, whereas before the training the participants' knowledge was only 15% regarding the KPI (Key Performance Indicators) method. Apart from that, in terms of training implementation, it can be concluded that 95% of the analysis results stated that the training had been carried out well, the material presented was clear, and 80% of participants stated that the training material was useful for practicing resource management at Bali Beach Glamping.